2019
DOI: 10.1016/j.bbmt.2019.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Cell Transplantation in the Treatment of Adult Acute Lymphoblastic Leukemia: Updated 2019 Evidence-Based Review from the American Society for Transplantation and Cellular Therapy

Abstract: The role of hematopoietic cell transplantation (HCT) in adults with acute lymphoblastic leukemia (ALL) is reviewed and critically evaluated in this systematic evidence-based review. Specific criteria were used for searching the published literature and for grading the quality and strength of the evidence and the strength of the recommendations. A panel of ALL experts developed consensus on the treatment recommendations based on the evidence. Allogeneic HCT offers a survival benefit in selected patients with AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 121 publications
1
34
0
1
Order By: Relevance
“…Presently, some researchers demonstrated that 3-year OS was 83% in patients who did not undergo SCT in first remission (ASH 2019), however, the current recommendation is the pursue allo-SCT for Ph + ALL (57)(58)(59). A consensus of North American experts also indicates that allo-SCT is an alternative method either for Ph+ ALL with negative pre-transplant MRD or for cases with positive pre-transplant MRD (7).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, some researchers demonstrated that 3-year OS was 83% in patients who did not undergo SCT in first remission (ASH 2019), however, the current recommendation is the pursue allo-SCT for Ph + ALL (57)(58)(59). A consensus of North American experts also indicates that allo-SCT is an alternative method either for Ph+ ALL with negative pre-transplant MRD or for cases with positive pre-transplant MRD (7).…”
Section: Discussionmentioning
confidence: 99%
“…In acute lymphocytic leukemia (ALL), the necessity of TBI has also been challenged in comparison to a BU IV-based chemotherapy. The MD Anderson group demonstrated a similar outcome to a TBI-based myeloablative (MA) alloHCT for ALL, albeit with different relapse and toxicity profiles [75,76]. However a recent randomized trial in pediatric patients with ALL demonstrated that TBI plus etoposide conditioning resulted in an improved overall survival (OS) and lower relapse risk [77].…”
Section: Methods To Minimize the Dose Of Tbimentioning
confidence: 99%
“…The transplantation of hematopoietic stem and progenitor cells (HSPC) from human bone marrow (BM), adult mobilized peripheral blood (MPB) or umbilical cord blood (CB) has for more than 50 years been employed as an effective treatment for a variety of blood disorders and malignancies ( Juric et al, 2016 ; Takami, 2018 ; DeFilipp et al, 2019 ). An important approach to assess their potency and predict the likelihood of robust engraftment is to determine the number and quality of lineage-specific progenitor cells and multipotent stem cells among the cells to be transplanted.…”
Section: Automated Classification and Quantitation Of Colonies Of Blomentioning
confidence: 99%